Spectrofluorimetric Determination Method for Pregabalin in Dosage Forms Using 9-Fluorenylmethyl Chloroformate: Spectrofluorimetric determination of pregabalin - Souri, Effat; Haramipour, Hamed; Barazandeh Tehrani, Maliheh; Shabani Ravari, Nazanin; Hariri, Roshanak (Iranian Journal of Pharmaceutical Sciences, 2023)
The present study produces a new, accurate, and simple spectrofluorimetric technique for the determination of pregabalin after derivatization with 9-fluorenylmethyl chloroformate in mild basic medium. Pregabalin, containing a primary amine group, reacts with 9-fluorenylmethyl chloroformate, a fluorophore reagent, in borate buffer and produces a fluorescent derivative. The maximum fluorescence intensity of the derivative and reagent was obtained at 315 nm after excitation at 280 nm. The fluorescence intensity of the reagent increases after derivatization with pregabalin, and the difference in the fluorescence intensity is proportional to the concentration of pregabalin. Experimental parameters which affect the derivatization reaction were studied. The best derivatization reaction between pregabalin and 9-fluorenylmethyl chloroformate was obtained after 30 sec. when 40 µg mL-1 of the reagent was used in a borate buffer of pH 9.0. Under optimized conditions, the linearity range (6-150 µg mL-1) of the method with a correlation coefficient of r2 0.9998, accuracy (Error<1.7%), and precision (CV<2.0%) was acceptable. The validated method was utilized for quantifying pregabalin in dosage form without interferences and showed good agreement with a reference method.